Optimal power flow for voltage stability improvement by using evolutionary programming optimization technique / Mohd Helmi Mansor - Mansor, Mohd Helmi (2007)
This project presents a methodology for solving Optimal Power Flow (OPF) problem by using Evolutionary Programming (EP) Optimization technique in order to improve the voltage stability, minimize the cost of generation and minimize the losses in the power system. This study has developed the Evolutionary Programming (EP) optimization technique using MATLAB software. The study tested three fitness functions namely total cost minimization, total loss minimization and the voltage stability improvement in power system. Comparison in the results obtained was made in order to determine the best fitness function to be used for solving OPF and hence the voltage stability is improved. The proposed technique was tested on the IEEE 26- - v./ bus reliability test system.